Discrimination between two sibling species of Acroperus (Baird, 1843) from the Palearctic (Cladocera: Anomopoda: Chydoridae) - Sinev, Artem Y. (Zootaxa, 2009)
Morphology and differential diagnosis of two common Eurasian but frequently confused Eurasian cladocerans, Acroperus harpae (Baird, 1834) and A. angustatus Sars, 1863, was investigated. Validity of both species is confirmed. A significant intraspecific variation in body shapes, unusual for species of the family Chydoridae, is present in females of both species. This “traditional” character is unreliable as diagnostic feature. Prominent differences between two species are revealed in antennal morphology, used for identification of all instars of males and females. Detailed morphology of males, postembryonal development of both males and females was studied in details for the first time. Our data suggest that two other European Acroperus taxa, A. neglectus Lilljeborg, 1900 and A. alonoides Hudendorff, 1876, are junior synonyms.